2021
DOI: 10.1007/s40123-021-00356-z
|View full text |Cite
|
Sign up to set email alerts
|

Demodex Infection Changes Ocular Surface Microbial Communities, in Which Meibomian Gland Dysfunction May Play a Role

Abstract: Introduction: Demodex and bacteria are both components of the ocular surface micro-ecology, constituting a complex interaction. This study aims to explore how ocular surface Demodex infestation (DI) affects ocular surface microbial communities and diversity. Methods: We recruited 255 subjects, and examined the correlation between ocular surface mite infestation and clinical indicators such as age, blood glucose level, dry eye symptoms, and blood pressure. 16S rRNA sequencing was performed on the conjunctival s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Yan et al's study demonstrated different results, which reported a higher RA of Firmicutes in the DB group than the healthy controls, and no significant differences in Proteobacteria and Actinobacteria between two groups (Yan et al, 2020). However, some other studies reported similar results to our study, with a higher RA of the phyla Proteobacteria in MGD or patients with Demodex infestation than in healthy controls (Lee et al, 2012;Dong et al, 2019;Liang et al, 2021). Combined with the results of the LEfSe analysis of conjunctival swab and meibum samples, an increased prevalence of the Proteobacteria phylum may be an indicator of an unstable ocular microbial community, as also found in gut microbiota (Shin et al, 2015;Litvak et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Yan et al's study demonstrated different results, which reported a higher RA of Firmicutes in the DB group than the healthy controls, and no significant differences in Proteobacteria and Actinobacteria between two groups (Yan et al, 2020). However, some other studies reported similar results to our study, with a higher RA of the phyla Proteobacteria in MGD or patients with Demodex infestation than in healthy controls (Lee et al, 2012;Dong et al, 2019;Liang et al, 2021). Combined with the results of the LEfSe analysis of conjunctival swab and meibum samples, an increased prevalence of the Proteobacteria phylum may be an indicator of an unstable ocular microbial community, as also found in gut microbiota (Shin et al, 2015;Litvak et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…Lee et al investigated bacterial 16S rRNA genes of eyelash and tear samples from 7 blepharitis patients with Demodex infestation and 4 healthy controls using a pyrosequencing method (Lee et al, 2012); and they reported that an increase of Staphylococcus, Streptophyta, Corynebacterium, and Enhydrobacter, and a decrease of Cutibacterium were observed from blepharitis subjects, in terms of the relative abundances. Liang et al used 16S rRNA sequencing to analyze the conjunctival swab samples of 14 MGD patients with ocular Demodex infestation and 17 healthy people, and reported that Pseudomonas, Acinetobacter, and Bacillus were the top three genera in all subjects, and there were more Acinetobacter, Novosphingobium, and Anoxybacillus in the Demodex infestation subjects and fewer Novosphingobium, Lactobacillus, and Candidatus Microthrix in the healthy control group (Liang et al, 2021). Yan et al also analyzed bacterial 16S rRNA genes of conjunctival swab samples from 30 Demodex blepharitis patients and 14 healthy controls, and demonstrated a significantly higher RA of genus Lactobacillus and Bifidobacterium in Demodex blepharitis patients, while the RAs of genera Cutibacterium and Streptococcus were not statistically different from normal controls (Yan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demodex mites could cause microstructural changes in the MGs, with more severe structural damage in MGD [ 29 , 30 ]. Lee et al [ 10 ] reported that Demodex had been associated with dry eye but not necessarily with aqueous tear deficiency, and patients with mite infestation might have normal Schirmer test scores.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular mite infection is significantly correlated with dry eye, MGD, and age. When Demodex mites infect the margin of the eyelid, the skin of the margin of the eyelid, the hair follicles and glands of the eyelid, and the meibomian glands will accumulate mites, and symptoms related to dry eye will occur ( 138 ). In addition, a typical clinical manifestation of Demodex blepharitis is cylindrical dandruff at the root of the eyelash, and this is considered pathognomonic for Demodex blepharitis ( 139 ).…”
Section: Tear Examinationmentioning
confidence: 99%